MELESTARIKAN BAHASA SUNDA SEBAGAI UPAYA MENJAGA WARISAN DAN NILAI ISLAM PADA SISWA KELAS 2 SDIT NURALIMA - Nani Rohani; Chika Gianistika; Diah Widiawati (Prodi PGMI STAI Sabili Bandung, 2026)
This study aims to determine the importance of preserving the Sundanese language with digital learning media as an effort to maintain Islamic heritage and values ​​in grade 2 students of SDIT Nuralima. The type of research used is descriptive qualitative research with a classroom action research design. The research method was carried out through observation, interviews, and documentation of students' daily learning and communication activities. The study population was all 72 students in Grade 2 of SDIT Nuralima, with a research sample of 15 students selected using purposive sampling. The research results show that the use of Sundanese in schools is still implemented through lessons, daily conversations, and school cultural activities. Teachers and parents play a crucial role in fostering polite Sundanese use in accordance with Islamic values, such as etiquette, good manners, and respect for elders. However, the development of digital technology and the use of social media have led to a decline in students' interest in using regional languages. The conclusion of this study is that preserving the Sundanese language as an effort to maintain Islamic heritage and values ​​in grade 2 students of SDIT Nuralima needs to be carried out jointly by schools, families, and the community so that cultural heritage is maintained and can be a means of instilling Islamic values ​​in children from an early age.